Treatment of Febrile Neutropenia and Prophylaxis in Hematologic Malignancies: A Critical Review and Update - Paola Villafuerte-Gutierrez; Lucia Villalon; Juan E. Losa; Cesar Henriquez-Camacho (Advances in Hematology)
Febrile neutropenia is one of the most serious complications in patients with haematological malignancies and chemotherapy. A prompt identification of infection and empirical antibiotic therapy can prolong survival. This paper reviews the guidelines about febrile neutropenia in the setting of hematologic malignancies, providing an overview of the definition of fever and neutropenia, and categories of risk assessment, management of infections, and prophylaxis.